Climate change and landscape-use patterns influence recent past distribution of giant pandas. Issue 1929 (24th June 2020) - Tang, Junfeng; Swaisgood, Ronald R.; Owen, Megan A.; Zhao, Xuzhe; Wei, Wei; Pilfold, Nicholas W.; Wei, Fuwen; Yang, Xuyu; Gu, Xiaodong; Yang, Zhisong; Dai, Qiang; Hong, Mingsheng; et al.
Abstract : Climate change is one of the most pervasive threats to biodiversity globally, yet the influence of climate relative to other drivers of species depletion and range contraction remain difficult to disentangle. Here, we examine climatic and non-climatic correlates of giant panda ( Ailuropoda melanoleuca ) distribution using a large-scale 30 year dataset to evaluate whether a changing climate has already influenced panda distribution. We document several climatic patterns, including increasing temperatures, and alterations to seasonal temperature and precipitation. We found that while climatic factors were the most influential predictors of panda distribution, their importance diminished over time, while landscape variables have become relatively more influential. We conclude that the panda's distribution has been influenced by changing climate, but conservation intervention to manage habitat is working to increasingly offset these negative consequences.